Effects of Hydroxycinnamates and Exogenous Yeast Assimilable Nitrogen on Cider Aroma and Fermentation Performance. (4th July 2022) - Cairns, Paulette; Hamilton, Leah; Racine, Kathryn; Phetxumphou, Katherine; Ma, Sihui; Lahne, Jacob; Gallagher, Daniel; Huang, Haibo; Moore, Amy N.; Stewart, Amanda C.
Abstract: Cider apple cultivars typically contain high concentrations of tannins (phenolic compounds) and/or acids. The phenolic content of some cider apples far exceeds that of white wine grapes, yet modern global cider styles are often fermented using yeast strains originally selected and commercialized for white wine production. The potential for phenolic compounds in cider apple juice to influence fermentation rate or aromas generated during cider fermentation is not typically considered in yeast strain selection. The objective of this study was to determine the impact of ferulic acid, p -coumaric acid, and chlorogenic acid (at concentrations reported in apples) on fermentation kinetics and cider aroma, and the interactive effects of yeast assimilable nitrogen (YAN) on these outcomes. Our hypothesis was that phenolic compounds present in high-tannin cider apples would slow down fermentation, but not alter aroma, and that added YAN would moderate these effects. Ferulic acid negatively affected fermentation performance ( p < 0.05 ), but p -coumaric and chlorogenic acids did not. A sensory sorting task showed that p -coumaric acid led to distinct differences in grouping by aroma, while ferulic acid resulted in distinct aroma descriptors. Finally, addition of YAN improved fermentation performance for low concentrations of ferulic acid, and it affected the aroma of cider amended with p -coumaric acid. Supplemental data for this article is available online at at [publisher's weblink].